Safeguarding Constitutional Democracy: The Role Of The Indonesian Constitutional Court Through Formal Review - Firdaus, Fahmi Ramadhan; Anggono, Bayu Dwi (Faculty of Law, Universitas Pasundan, 2025)
A good law is not only seen from the material aspect, but also a complementary side to the formal element as well as a factor in whether the law can be said to be good, especially in standings of the process of its making. The law-making progression is democratic; this process cannot be separated from public participation as the highest sovereign holder. However, there is a problem that public aspirations have not been meaningfully accommodated in the law-making progression as a form of substantive democracy. Hence, a formal checks-and-balances review in the Constitutional Court attempts to maintain democracy. Through a normative juridical approach, this study aims to explain the symptoms of a democratic crisis in Indonesia's law-making process and how the Constitutional Court's role protects democracy through a formal review of laws. The results of the research showed that legislators have not implemented democracy optimally, as evidenced by the neglect of the public's role in several processes of law-making processes and by the being of Constitutional Court Decision No. 91/PUU-XVIII/2020, which encourages the strengthening of democracy by prioritizing evocative civic involvement in the law-making progression.